Green and fast biodiesel production at room temperature using soybean and Jatropha curcas L. oils catalyzed by potassium ferrate. (20th October 2022) - Gutiérrez-López, Adriana N.; Mena-Cervantes, Violeta Y.; González-Espinosa, Mario A.; Sosa-Rodríguez, Fabiola S.; Vazquez-Arenas, Jorge; Rodríguez-Ramírez, Ricardo; Hernández-Altamirano, Raúl
Abstract: The biodiesel production is typically conducted around 65 °C (methanol's boiling point), this study describes a catalytic process at room temperature (25 ± 3 °C) to shrink energy consumptions. In order to achieve this, potassium ferrate (K2 FeO4 ) is used as a heterogeneous pseudo-catalyst in the transesterification reaction of two different vegetable oils: refined soybean oil (SBO) and crude Jatropha curcas L. oil (JCO). Transesterification variables are optimized using a Box-Behnken design (BBD) to maximize the oil conversion to fatty acid methyl esters (FAMEs). Process variables such as stirring rate (125–700 RPM), K2 FeO4 dosage (0.15–6 wt%), and methanol to oil molar ratio (6:1 to 16:1) are varied to obtain maximum conversion. The experimental results revealed that maximum conversion of 98.17% and 98.35% are produced in 1 h using the optimized conditions determined with the response surface methodology (RSM) for JCO (357 RPM, 5.29 wt% K2 FeO4 dosage, 14.89:1 MeOH: oil molar ratio) and SBO (700 RPM, 4.82 wt% K2 FeO4 dosage, 14.28:1 MeOH: oil molar ratio), respectively. The conversion percentage is quantified by Fourier Transform Infrared Spectroscopy (FTIR) and corroborated by proton nuclear magnetic resonance ( 1 H NMR). The fatty acid methyl esters produced under optimized reaction conditions are characterized to obtain their density, viscosity, acid number, oxidative stability, flash point, heating value, cloud point, and pour point to determine the quality compliance with the standard ASTM D6751 . Additionally, conversion percentage is monitored at 0, 1, 5, 10, 15, 30, 45, 60, and 90 min of reaction. It is found that after 5 min of transesterification reaction, a conversion of 98.31% is reached without significant variation over time using SBO. A similar conversion (98.07%) is generated at 30 min for JCO, reaching its maximum conversion (98.65%) at 90 min. These fast reactions might occur due to the methoxy radicals formed on K2 FeO4, unlike the methoxy ions produced by other heterogeneous catalysts. X-ray diffraction (XRD) and scanning electron microscopy (SEM) spectroscopy are used to characterize the K2 FeO4 material. Graphical abstract: Image 1 Highlights: K2 FeO4 catalyst does not require heat to produce biodiesel. Conversion of 98.07% is reached after 30 min using Jatropha curcas L. oil. Conversion of 98.31% is reached after 5 min using soybean oil. Fast transesterification reaction proceeds due to methoxy radical formation. Catalyst load and stirring rate are strong requirements to increase conversion.